Investigations by the Institut Hospitalo-Universitaire Méditerranée Infection of food and food-borne infections in the Mediterranean Basin and in sub-Saharan Africa. (November 2018) - Abat, C.; Rolain, J.-M.; Colson, P.
Abstract: Food-borne infections are major causes of public health concern in developing and developed countries. During the past decade, the Institut Hospitalo-Universitaire Méditerranée Infection has conducted or been involved in multiple investigations that aimed at identifying the sources and strains responsible for food-borne diseases and therefore at improving the understanding, diagnosis, prevention and control of these infections. Investigations were conducted in the Mediterranean area and in sub-Saharan Africa on more than 15 food-borne agents, 17 food products and 14 antibiotic resistance-associated genes. Multiple sources, including unexpected ones, and pathogens, including emerging ones, were involved. Travelling in developing countries and zoonoses are major contributors to food-borne infections, while food-borne transmission of resistance-associated genes is increasingly reported. However, risk factors and pathogens associated with food-borne infections likely remain untapped and must be more extensively investigated, monitored and regularly reassessed. Diagnostic tests based on new technologies and real-time surveillance tools based on microbiology laboratory data are promising approaches to detect known food-borne infections and decipher new ones. Studies of the microbiota and its relationships with dietary patterns are also worth being conducted.